Africa Agriculture Transformation Scorecard: Performance and Lessons. Botswana - Greffiths, Ikhothatseng Jacob; Matchaya, Greenwell C.; Kebonilwe, D.; Fakudze, Bhekiwe; Baemedi, G. (Regional Strategic Analysis and Knowledge Support System for Eastern and Southern Africa, 2023)
The Malabo Declaration on accelerated agricultural growth and transformation for shared prosperity and improved livelihoods is a set of goals that were adopted by Heads of State and Government of the African Union in 2014 in Malabo, Equatorial Guinea (AUC 2014). To translate the seven Malabo commitments into results, a call for action was made by the Heads of State and Governments, by calling upon the AU Commission and the NEPAD Planning and Coordinating Agency, in collaboration with partners, to initiate a review process to be conducted on a biennial basis starting 2017, with an objective of tracking, measuring, and reporting progress towards achieving the Malabo Declaration commitments by 2025. Three Biennial Reviews (BR) have been conducted—the inaugural BR in 2017, the second BR in 2019, and the third and most recent BR in 2021. This brief draws on the third BR report to summarize Botswana’s performance in pursuit of the seven Malabo Declaration commitments across the three BR cycles, highlights challenges and lessons from the third BR, and outlines policy and programmatic measures required for the country to meet the Malabo targets by 2025. The third BR reveals that Botswana is not on-track for achieving the Malabo Declaration commitments. However, the analysis notes an improvement in the country’s overall performance score since the second BR cycle. This progress from the second to the third BR indicates a turnaround from the decline the country registered between the first and second BR cycles. A key recommendation from the analysis is for the country to enhance its resilience to climate change by providing sufficient public funding. The country should also establish government budget lines to respond to spending needs on resilience-building initiatives.